Propaganda Kelompok Feminis Melalui Pemanfaatan Media Sosial Instagram - Nadindra Wastitya; Poppy Setiawati Nurisnaeny; M. Yusuf Samad (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Feminism has the main goal of equalizing the rights of women and men who were previously differentiated based on gender. The massive and comprehensive development of feminist groups through various media, one of which is using Instagram, is a means of spreading propaganda for feminist groups and supporting LGBT groups through feminist groups. In its use, Instagram as a means of propaganda takes advantage of its fast and wide spread so that the propaganda is carried out more effectively. The account @indonesiafeminis as a feminist and LGBT propagandist relies on illustrations, persuasive texts and videos to get the attention of the general public as social media users. This study aims to analyze the threat of propaganda in uploads from Instagram accounts related to LGBT. The theory used is the theory of Modern Propaganda and Threat Theory by analyzing a number of uploads on the account @indonesiafeminis. The result of the research is that the threat analysis shows that the @indonesiafeminis account has intentions and capabilities which are marked by intentions in the form of propaganda in support of LGBT and capabilities in the form of actions taken and social networks that are owned both in the real world and social media. Future researchers should conduct research by comparing several other feminist accounts and then analyze them comprehensively using other threat theories so that the suggestions from their research are also comprehensive.